A RESEARCH ABOUT THE RELATIONSHIP BETWEEN EMOTIONAL COMMITMENT AND EMPLOYEE PERFORMANCE - Meral ÇALIŞ DUMAN (Fırat University, 2019)
The value of the employee performances and emotional commitment is noticed some more day by day and rises in importance for today’s businesses whose things get difficult thoroughly with change and competition. Emotional commitment is an important necessity for employee performance. Especially for service sector, retaining competitive advantage, qualities which personnel have and sincere commitment to organization starts to be related directly. For that reason, the aim of this search; is determining the effects of the emotional commitment of the employee on performance and revealing what type of effect emotional commitment has on employee performance. In this context, datas were collected through survey on administrative personnel working at The University of Inonu which is active in the city of Malatya. In the result of the search, it was identified a positive and significant relationship between employee performance and emotional commitment.